TWO-SIDED FOCUSING OF ELECTROMAGNETIC FIELD OF POINT SOURCE BY MEANS OF PLANAR LENS FROM METAMATERIALS - V. T. Erofeenko (Informatika)
An analytical solution of the boundary-value problem of penetration of electromagnetic field of magnetic dipole through the planar lens from the focusing materials is suggested. It is demonstrated, that for the lenses from focusing materials two focuses are formed: first is over the screen and the second is in front of the screen in the source area. The field of focus in front of the lens is equal to the sum of the fields of magnetic and electric dipoles.